Rancang Bangun SINKER (Sistem Inventori Alat-Alat Kerja) Berbasis Website - Padeli Padeli; Refauza Refauza; Muhammad Rizky Awaluddin (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
Information Technology plays an important and dominant role in a business or operational management process in the company. So with the development of the role of the world of Information and Technology, computer processes are used not only as data processing. but a computer can be a media of information that can be accessed at any time. The application of the inventory system provides many benefits for companies to be able to improve company performance more effectively and efficiently. In carrying out the inventory data reporting is still using office-based applications, namely Microsoft Excel, which causes results that are not optimal. Then a web-based inventory application system was built. In determining research and research design requires a method to see the development of the design and research, the methods applied include the SWOT method to identify strengths (weaknesses), weaknesses (Weakness), opportunities (Opportunities), and threats (Threat) in the system that is researched, where a website system that has been designed with PHP Framework Codeigniter as a programming language and SQL as database storage. To design an inventory application system using Unified Modeling Language (UML) as a modeling tool consisting of Use Case Diagrams, Sequence Diagrams, and Activity Diagrams. The results of the web-based work tool inventory application system are expected to provide solutions to the problems faced